PENERAPAN MODEL ROLE PLAYING DENGAN METODE BRAINSTORMING UNTUK MENINGKATKAN HASIL BELAJAR AKUNTANSI - Halimah, Siti Nur; ., Sudiyanto; Muchsini, Binti (Tata Arta : Jurnal Pendidikan Akuntansi, 2017)
ABSTRACTThe objectives of this research are to improve: (1) the learning result in the cognitive domain through the implementation of role-playing model with brainstorming method to improve the studentsâ study result in the cognitive domain, (2) the learning result in the affective domain through the implementation of role- playing model with brainstorming method, and (3) the learning result in the psychomotor domain through the implementation of role-playing model with brainstorming method. This research used the classroom action research with two cycles. Each cycle consisted of planning, implementation, observation, and reflection. Its subjects were 30 students in Grade XI Accounting 2. The data of research were collected thorugh observation sheets of studentsâ activity for the affective and psychomotor study result and evaluation test for cognitive study result. The instruments of research were validated by using the content and construct validity. The data of research were analyzed by using the statistical descriptive comparative analysis by comparing the learning completeness percentage and average grade of the studentsâ learning result, as well as critical analysis technique to compare the advantages and disadvantages of the perfomance of teacher and students during the process of action. The results of the research are as follows: Firstly, there is an improvement of the study result in cognitive domain. In cycle I, the number of students who attained the minimum learning completeness was 21 (70%) with the average score of 72. In Cycle II, it became 25 (83.3%) with the average score of 76. Secondly, there is an improvement of the study result in affective domain. In cycle I, the number of students who attained the minimum learning completeness was 19 (63%). In Cycle II, it became 77 (23%). Finally, there is an improvement of study result in the psychomotor domain. the number of students who attained the minimum learning completeness was 20 (67%). In Cycle II, it became 24 (80%).Keywords: Role Playing, Brainstorming, The Study Result.ABSTRAKPenelitian ini bertujuan untuk meningkatkan (1) hasil belajar siswa pada ranah kognitif melalui penerapan model role playing dengan metode brainstorming; (2) hasil belajar siswa pada ranah afektif melalui penerapan model role playing dengan metode brainstorming; dan hasil belajar siswa pada ranah psikomotorik melalui penerapan model role playing dengan metode brainstorming. Subjek dalam penelitian ini adalah siswa kelas XI Akuntansi 2 yang berjumlah 30 siswa. Penelitian ini menggunakan metode Penelitian Tindakan Kelas yang dilakukan dua siklus dan setiap siklus terdiri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Pengumpulan data yang dilakukan pada penelitian ini terdiri dari lembar observasi aktivitas siswa untuk data hasil belajar ranah afektif dan psikomotorik, serta tes evaluasi untuk data hasil belajar ranah kognitif. Validitas instrumen menggunakan uji validitas isi dan konstruk. Teknik analisis data yang digunakan adalah teknik analisis statistik deskriptif komparatif dengan membandingkan persentase ketuntasan dan nilai rata-rata hasil belajar siswa, serta teknik analisis kritis dengan membandingkan kelemahan dan kelebihan kinerja guru dan siswa selama proses tindakan. Hasil penelitian adalah sebagai berikut. Pertama, ada peningkatan hasil belajar siswa pada ranah kognitif, yaitu perolehan persentase ketuntasan siswa pada siklus I sebesar 70% (21 siswa) dengan nilai rata-rata sebesar 72 dan pada siklus II mengalami peningkatan dengan perolehan sebesar 83,3% (25 siswa) dengan nilai rata-rata siswa sebesar 76. Kedua, ada peningkatan hasil belajar siswa pada ranah afektif, yaitu perolehan persentase ketuntasan siswa pada siklus I sebesar 63% (19 siswa) dan pada siklus II mengalami peningkatan dengan perolehan sebesar 77% (23 siswa). Ketiga, ada peningkatan hasil belajar siswa pada ranah psikomotorik, yaitu perolehan persentase ketuntasan siswa pada siklus I sebesar 67% (20 siswa) dan pada siklus II mengalami peningkatan dengan perolehan sebesar 80% (24 siswa).Kata Kunci : Role Playing, Brainstorming, Hasil Belajar